1957
DOI: 10.1002/hlca.19570400510
|View full text |Cite
|
Sign up to set email alerts
|

Ulein, das Hauptalkaloid von Aspidosperma ulei Mgf.Aspidosperma‐Alkaloide, 1. Mitteilung

Abstract: Aus der Wurzelrinde von Aspidosperma ulei Mgf. wurde in ca. 0,6‐proz. Ausbeute ein bisher nicht beschriebenes Dihydro‐carbazol‐Alkaloid, Ulein genannt, isoliert, für welches auf Grund von Abbauresultaten verschiedene Strukturen diskutiert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

1959
1959
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Les ouvrages relatifs à l'étude pharmacologique soulignent également l'importance de l'association des deux sites électroactifs observés [23]. D'une part.…”
Section: Cshsunclassified
“…Les ouvrages relatifs à l'étude pharmacologique soulignent également l'importance de l'association des deux sites électroactifs observés [23]. D'une part.…”
Section: Cshsunclassified
“…1) from ochrosia elliptica [1] and other plants [2] in the late 1950s, which was soon followed by the first total synthesis of ellipticine by Woodward [3], there has been steadily growing interest in this class of tetracyclic compounds. In particular, the discovery of the pronounced antitumour activity of the pyridocarbazoles [4,5] has stimulated further investigations in this field, leading to enhanced synthetic routes to the natural products as well as to a variety of structural modifications thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Slructure-activity studies of thèse tricyclic neuroleptics (dibenzoazepines) have shown the importance of the nature of the basic side-chain for binding to the receptor. Moreover, the substitution in one of the benzène rings is essential for strong neuroleptic activity [10][11][12][13][14][15][16].…”
Section: Introducmonmentioning
confidence: 99%